Arrangements of actin filaments in the cytoskeleton of human platelets. - White, J. G. (1984)
Assembly of actin molecules into filaments is closely associated with platelet shape change and exercise of contractile function. Since assembled actin filaments serve both as a framework for distortion of discoid shape and for generation of contractile force, it is important to determine the organizations of actin filaments capable of serving the two opposed functions of distortion and contraction. The present study has used negative staining alone and after combined glutaraldehyde fixation and detergent extraction to examine the arrangements of actin filaments in the cytoskeletons of surface activated platelets. Actin filament assembly developed as one of the earliest manifestations of platelet activation. Small protuberances containing random networks of actin filaments extending beyond the circumferential microtubules appeared to be an initial step in the response to stimulation. Transformation into dendritic forms was associated with development of parallel bundles of actin filaments organized into paracrystalline lattices with a periodicity of 5.5 nm at an angle of 60 degrees with the long axis of the pseudopod. Parallel bundles of actin filaments formed the concave borders of late dendritic forms and expanded to become the convex margin of most spread cells, suggesting a possible role in the spreading process. Other bundles of actin filaments resembled stress fibers radiating through the cytoplasm into pseudopods or organized in a variety of other apparently stable configurations. More loosely associated masses of actin filaments formed concentric layers around constricted rings of microtubules or a random network in the peripheral cytoplasm of spread cells. The arrangements of newly assembled actin filaments suggest their involvement in cell deformation, as well as contractile events.